Attitudes of young adults from the UK towards organ donation and transplantation - Coad, Laura (BioMed Central, 2013)
BACKGROUND: This study examines the attitudes of young British adults towards donating their own organs and those of their family members. METHODS: An opportunity sample of 119 participants (65 female) completed an attitude questionnaire. RESULTS: Most participants were in favour of donation though substantially fewer had signed up to the organ donation register. A minority of participants was aware of the proposed opt-out system for donation. CONCLUSIONS: The results from this study corroborate and extend previous work in that more participants were prepared to receive an organ than donate one. Knowing someone who had donated an organ was associated with a more positive attitude towards donation. Implications for policy are discussed.